If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -4) = 24 Reorder the terms: 3(-4 + 3x) = 24 (-4 * 3 + 3x * 3) = 24 (-12 + 9x) = 24 Solving -12 + 9x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 9x = 24 + 12 Combine like terms: -12 + 12 = 0 0 + 9x = 24 + 12 9x = 24 + 12 Combine like terms: 24 + 12 = 36 9x = 36 Divide each side by '9'. x = 4 Simplifying x = 4
| 3/6*8/4*2/3*6/3 | | X^2-5x-120=180 | | (6x^2+36x+28)/(x+5) | | 0.07q+0.7=0.17q-9.5 | | 9-6+u=(27-24)(2)+u | | -13+5h=12 | | 2x+14=5x+5 | | 56-(2x+13)=2(x+9)+x | | 5n+6=-7(5n-6)-6n | | (1/2x-1)^2+(1/2x-1)-72=0 | | 4x+7-6=54x+4 | | 2c^3+2c^2-4c=0 | | 9x^4+15x^3-36x^2-60x=0 | | 7.6p-3.1=42.5 | | 5.2=.04m | | 3(3x-12)=24 | | 13+1x=1 | | 2x+4-5x(x-5)=5x | | 2-6n=-5(4-n) | | -4(-8+2)=-4x-8 | | 2x^4-56x^2+150=0 | | 13x+12= | | -4c-18=-6c-8 | | 2x+10-6x=19-18x+14x-9 | | (3/5)x=15 | | -5/2=0.04m | | 5x+10=-2x+3 | | 9x-15=7x+11 | | -4=3n+2n | | 2a=5a+-15 | | 2x^2-66x+540=0 | | 13x+2001=2013 |